2018
DOI: 10.1177/2158244018809216
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Multiple Intelligence-Based Instructions Approach on Performance Improvement of Indonesian Elementary Madrasah Teachers

Abstract: Multiple intelligence (MI) theory has attracted much attention in the field of education, although Howard Gardner as the inventor of this theory, does not intend to create it to apply learning and instruction. The theory was directed at the philosophy of developmental and cognitive psychology (Gardner, 2011) as a discipline he was interested in since the beginning of his career. Eventually, MI theory became popular in educational practice. The typical studies, which connect MI and education, are becoming multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The findings of this study have evidently proven that students' multiple intelligences can be nurtured, stimulated and developed through several computer-based learning enrichment activities [5]- [3]. This study also recommends that vast opportunities should be given to the development of problem-based enrichment activities that can examine and support students' multiple intelligences [10]- [13]. Creative and innovative computerized multimedia learning materials should be widely used in unfolding and nurturing students' potentials.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The findings of this study have evidently proven that students' multiple intelligences can be nurtured, stimulated and developed through several computer-based learning enrichment activities [5]- [3]. This study also recommends that vast opportunities should be given to the development of problem-based enrichment activities that can examine and support students' multiple intelligences [10]- [13]. Creative and innovative computerized multimedia learning materials should be widely used in unfolding and nurturing students' potentials.…”
Section: Discussionmentioning
confidence: 83%
“…Table 1 illustrates the distribution of the selected sample. [13] and it has been modified and translated into Malay Language. The instrument has a high reliability value of .80 [9].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, we must consider that possibly the reason why students have little difference in the classifications of MI is that the teachers do not motivate their students to exercise it. There are certain studies where it has been found that the application of MI during class by teachers helps to improve the academic development of students (Dolati and Tahriri, 2017;Ghamrawi, 2014;Yaumi et al, 2018). In further research, this could be a better way to analyze MI by considering to study both the teacher and the students, not just one or the other.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher used Classroom Action Research (CAR) (Elliot, 1991;Kember, 2000;Yaumi, Sirate, & Patak, 2018). It was done through two cycles including trying out the portfolio assessment method, to test how much the portfolio assessment solves the students' writing problem.…”
Section: Methodsmentioning
confidence: 99%